Penerapan Objek Vital, Pengamanan File, Dan Pengamanan Cyber Pada Bank JABAR - Edy Soesanto; Alifah Jiddal Masyruroh; Ganis Aliefiani Mulya Putri; Srirahayu Putri Maharani (Lembaga Pengembangan Kinerja Dosen, 2023)
Information security and asset protection have become top priorities in the banking industry today. Bank JABAR (Jawa Barat), as one of the leading banks in the region, also recognizes the importance of effective security management. The objective of this research is to examine the implementation of vital objects, file security, and cyber security at Bank JABAR. This research uses a descriptive analysis method by studying the policies and practices implemented by Bank JABAR in information security. Data collection techniques include documentation study and interviews that cover security policies, guidelines, and procedures at Bank JABAR. The results of this research indicate that Bank JABAR has implemented vital objects by identifying critical assets or information and giving them appropriate protection priority. File security is implemented through strict access policies, data encryption, regular data backup and recovery, as well as secure data disposal. Cyber security is carried out through firewall policies, intrusion detection systems, continuous network monitoring, and regular system security updates. In conclusion, Bank JABAR has taken important steps in the implementation of vital objects, file security, and cyber security. However, there is a need for ongoing efforts to enhance security awareness, involve more intensive training, and adopt a proactive approach to information security.